Study on the protective effect of Lycopene on ischemia-reperfusion myocardium through Inhibiting the opening of mitochondrial MPTP and the activation of apoptotic pathway - WANG,Juan (2022)
Abstract Through in vitro experiments, the paper investigated whether Lycopene can mitigate cardiac ischemia/reperfusion injury, and further explored whether the underlying mechanism works by inhibiting the opening of MPTP.A hypoxia-reoxygenation model was established. CCK8 was employed to determine the viability of H9c2 cardiomyocytes. LDH was used to determine the degree of damage of H9c2 cardiomyocytes. Trypan blue staining was applied to determine the survival rate of H9c2 cardiomyocytes. Flow cytometry was used to determine the apoptosis rate of H9c2 cardiomyocytes. Rhodamine 123 staining method was applied to evaluate the changes of mitochondrial membrane potential of H9c2 cardiomyocytes. Western blot was employed to determine the protein expressions of related factors of MPTP downstream apoptosis pathway in H9c2 cardiomyocytes. Calcium induction method was used to evaluate the opening degree of MPTP of H9c2 cardiomyocytes. Western blot was applied to determine the protein expressions of the related factors regulating MPTP opening in H9c2 cardiomyocytes.The vitality of H9c2 cardiomyocytes in the Lycopene group was significantly improved, the LDH activity was significantly reduced, and the cell survival rate was significantly improved. The apoptosis rate was significantly reduced, and the membrane potential decreased significantly. The expression levels of Bax, cytochrome C, APAF-1, caspase 9 and caspase-3 proteins were significantly reduced. The sensitivity of MPTP opening was significantly decreased. Lycopene can effectively alleviate the hypoxia/reoxygenation injury of H9c2 cardiomyocytes. By up-regulating Bcl-2 and down-regulating Bax, Lycopene can inhibit the opening of mitochondrial MPTP and the activation of downstream apoptotic pathways, thereby reducing apoptosis.